1984
DOI: 10.1007/bf01410471
|View full text |Cite
|
Sign up to set email alerts
|

A review on drag reduction with special reference to micellar systems

Abstract: A state-of-the-art review on drag reduction has been presented in order to bring out some important aspects of the drag reduction phenomenon and its potential for practical use. The review is biased towards micellar systems and discusses in detail the morphological differences between drag reducing polymeric and micellar systems. Work relating to polymeric systems has not been dealt in detail as it has been the subject of earlier reviews. Studies relating to biological additives as well as suspensions have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
11

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 208 publications
(148 reference statements)
0
61
0
11
Order By: Relevance
“…As a result of the non-uniform stress distribution during experiments, these micelles are oriented such that their long axis is parallel to the flow direction in shear. Although, the mechanical stability of the anionic surfactant [13], but they seem to be degraded as shown in Fig.5, this degradation occurs as a result of break-up of the micelle microstructure due to high shear stresses that exceed critical stress. The decreasing in drag reduction can be also explained if we know that for anionic surfactant the spherical micelles usually aggregate into cylindrical micelles, which formed a network of interlaced rod-like elements and the aggregation forces of the surfactant molecules are overcome by the shear stress so the aggregates are broken down to small particles, which have little drag reduction ability.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the non-uniform stress distribution during experiments, these micelles are oriented such that their long axis is parallel to the flow direction in shear. Although, the mechanical stability of the anionic surfactant [13], but they seem to be degraded as shown in Fig.5, this degradation occurs as a result of break-up of the micelle microstructure due to high shear stresses that exceed critical stress. The decreasing in drag reduction can be also explained if we know that for anionic surfactant the spherical micelles usually aggregate into cylindrical micelles, which formed a network of interlaced rod-like elements and the aggregation forces of the surfactant molecules are overcome by the shear stress so the aggregates are broken down to small particles, which have little drag reduction ability.…”
Section: Resultsmentioning
confidence: 99%
“…Suspensions of macroscopic fibers and surfactants are also known to be drag-reducing (Radin et al, 1975;Metzner, 1977;Shenoy, 1984;Lin and Zakin, 2001). Drag reduction in fiber suspensions and surfactants is much less and much more dramatic than in polymer systems, respectively.…”
Section: Chapter 7 Future Workmentioning
confidence: 99%
“…This is the so-called "polymer drag reduction" phenomenon, and was first observed experimentally in 1940s (Lumley, 1969;Virk, 1975;McComb, 1990;Graham, 2004). Since then, it has been found that many other types of additives, including rigid fibers (Lee et al, 1974;Radin et al, 1975;Metzner, 1977), wormy micelle-forming surfactants (Shenoy, 1984;Lin and Zakin, 2001) and even micro bubbles (L'vov et al, 2005;Ortiz-Villafuerte and Hassan, 2006) With these definitions, the laminar-turbulent transition can be represented on a Prandtlvon Karman plot, U avg /u τ vs. log Re τ , shown schematically in Fig. 4.…”
Section: Introductionmentioning
confidence: 99%
“…This turbulent drag reduction phenomenon implies that pipe flow containing these additives requires a lower pressure drop for a given flow rate (Rozenblit et al, 2006, Nguyen et al, 2006. The characteristics of such a dilute surfactant solution have been investigated in oil well fracturing operations (Ousterhout and Hall, 1961), increasing the output of the water jet during fire fighting (Fabula, 1971), in transportation of crude oil in the Alaska and Norwegian pipelines (Sellin and Ollis, 1980;Burger et al, 1980), sewage systems to prevent overflow during heavy rains (Sellin and Ollis, 1980), in water supply and irrigation systems (Sellin et al, 1982 a, b;Shenoy, 1984), hydraulic transportation of solid particle suspensions (Golda, 1986), and closed-circuit pumping installations (Choi et al, 2000;Suzuki et al, 2005). A similar application is the addition of polymers to oil being pumped from offshore platforms to shore facilities (Beaty et al, 1984).…”
Section: Introductionmentioning
confidence: 99%